Nueva combinación para el género Thamnodynastes (Serpentes/ Colubridae) de Argentina - Cei, José Miguel Alfredo María (1992)
In accordance with a recent thorough research by Thomas and Bailey (in press), Thamnodynastes strigilis (Thumberg, 1787) was placed in synonymy of Thamnodynastes pallidus (Linnaeus, 1758). In the present paper the formerly named T. strigilis from Corrientes and neighboring Parana areas until riparian zone of Rio de La Plata, is shown to be identical to Tachymenis hypoconia Coope, i860, Terra typica Buenos Aires, Argentina, also included in the strigilis's synonymic list by Peters and Orejas Miranda, 1970. A new combination Thamnodynastes hypoconia (Cope, 1860) is here proposed and commented.